Furan-derived chiral bicycloaziridino lactone synthon: collective syntheses of oseltamivir phosphate (Tamiflu), (S)-pipecolic acid and its 3-hydroxy derivatives - Chavan, Subhash P.; Kadam, Appasaheb L.; Shinde, Shrikrishna S.; Gonnade, Rajesh G. (Chemistry-An Asian Journal, 2020)
A unified synthetic strategy for oseltamivir phosphate (tamiflu), (S)-pipecolic acid, and its 3-hydroxy derivatives from furan derived common chiral bicycloaziridino lactone synthon is described here. Key features are the short (4-steps), enantiopure, and decagram-scale synthesis of common chiral synthon from furan and its first-ever application in the total synthesis of biologically active compounds by taking the advantages of high functionalization ability of chiral synthon.
Keywords: Aziridine synthon; Chiral auxiliary; collective synthesis; Pipecolic acid; Tamiflu